Improved blood glucose level associated with polypeptide-K (Diabegard®), a polypeptide isolated from the seeds of Momordica charantia supplementation: evaluation of 6 cases - Yong, Yean Sirn; Lee, Cheng Lok; Ahmad, Zuraini; Abdullah, Muhammad Nazrul Hakim (Global Research Online Publishing House, 2014)
To describe six cases of glucose management in diabetic and pre-diabetic patients with Diabegard® supplementation. We report the clinical courses of six individuals taking Diabegard® supplementation at 60 and 120 mg/day for 8 weeks. Patients had a maximum of 50% reduction in fasting blood glucose with 42% reduction in glycated haemoglobin (HbA1c). Patients also had improved kidney functions (expressed by normal level of blood urea nitrogen, creatinine and urine microalbumin). In some patients, these three parameters were elevated prior to supplementation. These results suggest that supplementation of Diabegard® will improve patients' glucose management and with reduction of elevated blood glucose level, kidney functions will also improve. However, patients taking this supplementation are advised to seek medical consultation in monitoring their blood sugar levels.